IDENTIFIKASI KEARIFAN LOKAL SEBAGAI UPAYA UNTUK MENINGKATKAN DAYA TARIK WISATA DI KAWASAN EKOWISATA GUNUNG API PURBA NGLANGGERAN, KECAMATAN PATUK, KABUPATEN GUNUNGKIDUL - Sugiarto, Eko; Palupi, Angesti (Kepariwisataan: Jurnal Ilmiah, 2019)
Lokal wisdoms which are exist in the society of ecotourism area of Gunung Api Purba Nglanggeran can improve its tourism attraction in this area. However, this potential attraction has not been executed maximally. Therefore, identification towards its local wisdoms which are exist in the society of ecotourism area of Gunung Api Purba Nglanggeran is important to be conducted. This research used qualitative method. This study is aiming at identifying the local wisdoms which can improve tourism attraction in the ecotourism area of Gunung Api Purba Nglanggeran. This research showed that there are some local wisdoms that were successfully identified such as sacred places or places which has its folklore, customary law, belief, rituals, and arts. Those various local wisdoms have its beauty, uniqueness, and appropriate meaning that can improve tourism attraction in the ecotourism area of Gunung Api Purba Nglanggeran.Keywords: Local Wisdom, Tourism Attraction